2012
DOI: 10.1111/bdi.12027
|View full text |Cite
|
Sign up to set email alerts
|

The association of the effect of lithium in the maintenance treatment of bipolar disorder with lithium plasma levels: a post hoc analysis of a double‐blind study comparing switching to lithium or placebo in patients who responded to quetiapine (Trial 144)

Abstract: Nolen WA, Weisler RH. The association of the effect of lithium in the maintenance treatment of bipolar disorder with lithium plasma levels: a post hoc analysis of a double‐blind study comparing switching to lithium or placebo in patients who responded to quetiapine (Trial 144). 
Bipolar Disord 2012: 00: 000–000. © 2012 John Wiley & Sons A/S.Published by Blackwell Publishing Ltd.Objectives:  There is no robust proof that the efficacy of lithium in the prevention of manic and depressive episodes in bipolar d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 27 publications
1
46
0
Order By: Relevance
“…Factors associated with overall good prognosis of BD include good treatment adherence, lack of early adversity, intermediate age at onset, good social support, and the absence of spontaneous rapid cycling406, 407 or features of a personality disorder 408…”
Section: Maintenance Therapy For Bipolar Disordermentioning
confidence: 99%
“…Factors associated with overall good prognosis of BD include good treatment adherence, lack of early adversity, intermediate age at onset, good social support, and the absence of spontaneous rapid cycling406, 407 or features of a personality disorder 408…”
Section: Maintenance Therapy For Bipolar Disordermentioning
confidence: 99%
“…Concerning lithium, it has been reported that only at plasma levels between 0.6 and 1.2 mEq/lt it is efficacious in the prevention of both manic and depressive episodes (Nolen and Weisler, 2013). Another posthoc analysis did not confirm its efficacy in the prevention of depressive episodes while it confirmed the efficacy of lamotrigine in the prevention of both manic and depressive episodes irrespective of index episode (Calabrese et al, 2003a; Goodwin et al, 2004).…”
Section: Efficacy Datamentioning
confidence: 99%
“…The similarity in the efficacy of standard vs. ‘sub-therapeutic’ lithium levels that was observed in the BD treatment in the present study has been indirectly addressed by recent studies on BD (9,16). The LiTMUS study evaluated symptomatic BD; however, unlike the current study it was solely based on the use of lithium monotherapy (9).…”
Section: Discussionmentioning
confidence: 54%